Crop biomass and yield patterns of dominant agroforestry systems of Navsari district, Gujarat, India - Singh, Nongmaithem Raju; Arunachalam, A.; Dobriyal, Manmohan J.; Bhusara, J.B.; Gunaga, R.P. (Indian Journal of Agroforestry, 2020)
A preliminary survey was conducted during 2015-16 in Navsari District, Gujarat, India to document dominant agroforestry systems practiced by farmers of this region. Five dominant agroforestry systems are in practice i.e. agri-horticultural (AH), homegarden (HG), agri-silvi-horticultural (ASH), agri-silvicultural (AS) and horti-pastoral (HP). A total of 11 different trees and 22 agricultural crop species have been documented from these different agroforestry systems, in which all the 11 tree species and 14 agricultural crops were grown under homegarden system. In case of herb/weedy species, a total 30 plants were recorded from the five different agroforestry systems and the most extensively distributed plants were belonging to the family Amaranthaceae (Alternanthera sessilis and Amaranthus viridis). Saccharum officinarum under AS system and Cajanus cajan in HG system gave maximum above and belowground crop biomass, respectively. Oryza sativa during kharif season gave higher economic yield than crop grown during rabi season (Dolichos lablab and Cicer arientinum) in AH system. In HG system, Cymbopogon spp. recorded highest economic yield. Similarly, in ASH system, Solanum lycopersicum gave more yield than Abelmoschus esculentus and Solanum melongena.